THE IMPACT OF REMOTE WORK, WORKPLACE RELATIONSHIP, AND ORGANIZATIONAL CULTURE TOWARD BUSINESS PERFORMANCE (CASE STUDY AT PT. BERKAT MANDOLOKANG JAYA) - Fierro Palibutan; JAMES MASSIE; JULIO RUMOKOY (Universitas Sam Ratulangi, 2023)
This study examines the influence of remote work arrangements on business performance, focusing on the interconnected dynamics of workplace relationships and organizational culture. It explores the factors driving the shift towards remote work, such as technological advancements and changing employee preferences. The abstract highlights the importance of understanding the impact of remote work on various aspects of business performance and presents insights from existing literature and empirical studies in this field. Using a quantitative research approach, data were collected through a survey questionnaire distributed to the employees of PT. Berkat Mandolokang Jaya to 100 of their employees. The findings indicate that Remote Work has a significant positive influence on Business Performance as it fosters employee flexibility and facilitates the generation of new ideas. Furthermore, positive Workplace Relationships are shown to enhance Business Performance, highlighting the importance of fostering a harmonious work environment. Lastly, a strong Organizational Culture is found to significantly improve Business Performance, as it promotes a positive and cohesive atmosphere within the company. By investigating these variables, this research aims to provide valuable insights into the factors that contribute to the success of businesses in the evolving landscape of remote work. Keyword: remote work, workplace relationship, organizational culture, business performance